Private Gold Industry of Kuzbass in Late 19th - Early 20th Century - A. N. Ermolayev (Научный диалог, 2018)
The article is devoted to the history of the gold mining industry of Kuzbass in the late 19th - early 20th century. The purpose of this article is to establish the dynamics of gold mining in the Mariinsky and Kuznetsk taiga, as well as to identify the factors affecting the development of the gold industry in these areas. The results of studying the dynamics of gold mining is presented according to official published surveys in the province of Tomsk and Tomsk archival records of the Mining Department. It is shown that the private gold industry of Kuzbass in the late 19th century had significant differences: in the Kuznetsk taiga there were big companies and firms, and in the Mariinsky taiga - small ones. It is emphasized that in the Kuznetsk uezd gold mining was 3-4 times higher than in the Mariinsky. It is concluded that over time the situation has changed dramatically: before the First World War the gold industry in Kuznetsk uezd had decreased several times, and in the Mariinsky uezd, on the contrary, had grown more than 2 times. It is proved that the growth of the gold industry in the Mariinsky taiga is associated with the use of new technologies (the use of drag) and the beginning of the development of ore deposits. In the Kuznetsk uezd drags were not used, and ore deposits were not found. The author notes that the development of the gold industry in the Mariinsky uezd was facilitated by the construction of the Siberian railway, which passed through Mariinsk.